A duality model of dynamic capabilities: Combining routines and improvisation - Ana Carvalho (Administrative Sciences, 2023)
Dynamic Capabilities are predominantly conceptualised as being based on routine, stable patterns of behaviour. This is paradoxical with their intended purpose to elicit change in firms' resource base and operational capabilities that allows them to face highly dynamic environments. I contribute to resolve this paradox by bringing the concept of duality to the Dynamic Capabilities debate. In particular, I argue that the view of Dynamic Capabilities as routines stems from the misconception that reliable outcomes can be attained only through stable mechanisms. Drawing on the literature on routine dynamics and on improvisation, as well as the empirical evidence of previous research, I propose a duality model that conceives Dynamic Capabilities as based both on routines and on improvisation. This duality perspective highlights the interdependence and complementarity between predictable stable routines and extemporaneous improvised actions that are both necessary to reliably achieve the (often radical) change needed to compete in highly dynamic environments. Rather than dealing with stable routines and improvisation as a trade-off, organisations must dynamically strive for the right balance, managing them concurrently and synergistically.
Keywords: 350; duality; dynamic capabilities; improvisation; paradox; reliability; routines